Application of SAR Offset Tracking Based on Dynamic Window Using Local Features for Landslides in Mining Areas - Yuejuan Chen; Dejun Zhao; Pingping Huang; Weixian Tan; Bo Yin; Yaolong Qi; Xianglei Li; Yang Liu (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The inability of traditional offset tracking to adapt the feature window to changes in surface feature density limits its effectiveness in monitoring complex surface deformations. This study addresses this issue by proposing a local feature extraction method based on different coordinate grid areas and combining multiscale analysis and multiangle dynamic thresholds. The study uses principal component analysis to select the main variation components for local feature values and dynamically adjust the initial feature window method in conjunction with the variation coefficient. Finally, the study separately employs the structural time series model and spatial autocorrelation to evaluate and compare the performance of the dynamic window and the fixed window, using the offset results to analyze potential causes of landslides. The research indicates that the dynamic window size can effectively capture the complex characteristics of areas with severe deformation and ensure data integrity in landslide edge areas.